Conservative management of Retzius space hematoma following spontaneous vaginal delivery in a woman with an unscarred uterus: A case report - Erinna Mohamad Zon; Nik Rafiza Afendi; Mohd Pazudin Ismail; Adibah Ibrahim; Noor Adibah Hanum Che Hashim (Elsevier, 2022)
Introduction: A retroperitoneal hematoma in obstetrics is very rare following spontaneous vaginal delivery. It requires a high index of suspicion, especially in a hemodynamically unstable patient with no active bleeding or external trauma postpartum, as early intervention is needed to prevent maternal morbidity and mortality. Conservative management may be an appropriate strategy in managing large hematomas even though surgical evacuation is classically recommended. Case: We report the case of a 39-year-old woman, para three, with a hematoma of the Retzius space after spontaneous uncomplicated vaginal delivery. The patient had sudden abdominal pain associated with urinary retention, two hours after delivery. She had a palpable mass at the anterior upper part of the vaginal wall, near the fornices, but no abnormality was detected at the labia majora, labia minora and lower part of the vagina. A transabdominal ultrasound scan revealed a mixed-echogenicity mass between the bladder and lower part of the uterus measuring 110 × 90 × 60 mm. The patient's hemoglobin level dropped from 12 g/dL to 10 g/dL. Given the patient's clinically stable state, she was managed conservatively with antibiotics, analgesics and one unit of packed red blood cells, and was discharged home day 5 postpartum. Conclusion: This case supports the conservative management of even large Retzius space hematomas for hemodynamically stable patients. A high index of suspicion and thorough evaluation are required when encountering a complaint of urinary retention and abdominal pain postpartum.